Review of perception of police performance in streets, hospitals and Twitter in the Covid-19 era - García Lirios, Cruz (Passagens: Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal do Ceará, 2023)
The pandemic impacted the perception of safety through the anti-COVID-19 policies of social distancing and confinement. Violence against vulnerable groups moved from public spaces to neighboring areas and within the family. The perception of the police action in the face of Covid-19 was the objective of this work. A cross-sectional, psychometric and correlational study was carried out with a sample of 100 students, considering their participation in the public health system as social servants or professional practitioners through a platform. A four-factor structure was found that explained 63% of the total variance, although the findings are only applicable to the sample, and its extension to other scenarios is recommended.